Formação discursiva e os sistemas de classificação bibliográfica: impactos, desdobramentos e implicações na representação da informação da área da religião - Rosana Matos da Silva (2016)
In recent years, an understanding that Knowledge Organization Systems constitute technical instruments that are neutral from the point of view of its main function - representing information, has been the subject of critical questions and reviews. The present research had as objectivethe conception of discursive formation in the sciences of the religion area in interface with social-historical dimensions and their unfoldings, impacts and implications in systems of representation of the knowledge in light of the concept discursive formation of Foucault (2012). For this purpose, the Dewey Decimal Classification (CDD) and the Universal Decimal Classification (CDU) class was used as the empirical object. In order to operationalize such an approach, categories of analysis of the statements in the field of religious discourse have been delimited in order to observe as relations of which they are susceptible, recognizing the processes of information representation that can assert what controls both an order of appearance of the discourses, Its fading. In this way, in a first moment, to analyze the classificatory arrangement of the class of Religion verifying the discursive trajectory of formulations and to characterize it as according to its different significations in the context ofits successive discourses. Secondly, an analysis of the narratives of research subjects (Babalorixá, Scientist of Religion, Spiritist, Evangelical and Priest) composed of thematic categories, based on the extracts of the faults of the interviewees, were triangulated in categories of discourse marked by the theoretical reference adopted. The analytical effort of the relations between the library arrangements and the ways in which the subjects perceive the representation of knowledge allowed us to verify that the classificatory instrument sometimes reflects and dialogues little with how socio-cultural transformations are underway and can provoke irreparable misunderstandings in the processes of circulation Recover the information.